Social Media Influence on Youth Identity Formation in Urban Communities - Kartika, Rina; Puspita, Melati; Susanto, Joko (Journal Social Humanity Perspective, 2025)
This research studies how social media affects the identity construction of persons that are found in urban community and the research question is placed in the broader disciplinary huminge of management and organizational research. The high-speed and high rate of digital platform expansion has fundamentally altered the way young people select the structures by which identity, affiliation, and self-expression are experienced, more so in the vibrantly interconnected urban environment. Quantitative research design was adopted whereby survey data were restrictively tapped to the urban youth cohorts and in the next step analysed using descriptive and inferential statistics which include correlation analysis and implementing regression model and analysis of variance (ANOVA). The findings suggest that social media participation poses a strong relationship among the dimensions of identities such as self-presentation, peer affiliation and internalization of values, whereas consumption patterns, online interaction and management of visibility display strong social and organizational outcome and hence a growing fact and convergence between youth that relies on brand culture, political talks and consumer behaviours. The study contributes by filling gaps in the available literature that largely are of a qualitative or Western-dominated nature, giving the advantages of an empirical source of information based on a non-Western urban environment, and thus enhancing a more globally indicative perspective of identity formation during the digital age. These implications of these results are not limited to the sociological discourse, as they also can be actively implemented into the work of a manager in a variety of fields, including youth engagement, brand strategy, human resource development, policy programs designed to provide more people with digital literacy. Overall, the paper highlights that social media is both a transformative and a contentious space in which youth identities will be constructions, fights, and commodities as the mechanism of creating and constructing them knows no end within structural forces of urbanity life today.